2018
DOI: 10.3390/ijerph15061051
|View full text |Cite
|
Sign up to set email alerts
|

Human Mercury Exposure in Yanomami Indigenous Villages from the Brazilian Amazon

Abstract: In the Brazilian Amazon, where the majority of Yanomami villages are settled, mercury (Hg) exposure due to artisanal small-scale gold mining (ASGM) has been reported since the 1980s. This study assessed mercury exposure in the Yanomami reserve and whether the level of contamination was related to the ASGM geographical location. It was conducted using a cross-sectional study of 19 villages. Direct interviews were performed and hair samples were used as a bioindicator of Hg exposure. The Prevalence-Ratio (PR) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 35 publications
3
43
0
1
Order By: Relevance
“…These alliances extend to scientists because access to scientific information on pollution impacts has been important in spurring indigenous protests in many regions (Stetson 2012). For example, knowledge of high levels of Cd in their blood triggered a change in the resistance methods employed by the Achuar in the Corrientes River (Orta‐Martínez and Finer 2010) and the Yanomami in Brazilian Amazonia (Vega et al 2018). Based on their own experiences, some indigenous representatives have also travelled to warn others against accepting polluting industries on their lands (Kirsch 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These alliances extend to scientists because access to scientific information on pollution impacts has been important in spurring indigenous protests in many regions (Stetson 2012). For example, knowledge of high levels of Cd in their blood triggered a change in the resistance methods employed by the Achuar in the Corrientes River (Orta‐Martínez and Finer 2010) and the Yanomami in Brazilian Amazonia (Vega et al 2018). Based on their own experiences, some indigenous representatives have also travelled to warn others against accepting polluting industries on their lands (Kirsch 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This activity is generally coordinated by illegal networks and conducted by wildcat gold miners, and dealers [ 7 ]. ASGM has adversely affected the health of riverside communities—particularly indigenous people [ 8 , 9 ]—that rely on fish as their main protein source [ 10 , 11 ]. Fisheries in the Amazon provide food security and reduce malnutrition rates, as fish are the dominant dietary source of essential amino acids, lipids with fatty acids, minerals, and vitamins [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (FIOCRUZ, 2016;VEGA et al, 2018) have confirmed that indigenous communities living near facer mining activities carried out in Uraricoera River have shown worrisome levels of contamination with mercury -which is a toxic metal with bioaccumulation properties -mainly in the form of methylmercury, which leads to severe and permanent damages to human health (LARINI, 1997;GIBB;O´LEARY, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite state accountabilities and the acknowledged vulnerability of indigenous populations, the Yanomami people have been continuously exposed to the effects of mercury for at least three decades (VEGA, 2018). Studies have reported high contamination levels in communities living in Roraima State (CASTRO; ALBERT; PFEIFFER, 1991;SING et al, 2003;VEGA, 2018), but little is known about the direct clinical effects of this contamination on the health and well-being of these populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation